Lesson Study Implementation on Physics Students to Increase the Competence of PPG Students as Indonesian Prospective Teachers - H Husain*; Nurhayati, N.; Nurfadillah, R. (Physics Education, 2024)
The implementation of lesson study in the teaching process of physics education students during the PPL Program in the school aims to develop students' competence as future teachers through collaborative evaluation and continuous collaboration with other teachers. The observation results showed an increase in various competencies from cycles. The result of the pretest and posttest shows that the ratio of competence increased between students who thought by implementing lesson study and without implementing lesson study more than 2:1, which indicated that the implementation of lesson study could be implemented to increase teacher competence in the future. The qualitative analysis also shows that PPG students and students can benefit from lesson study, especially in developing knowledge and positive attitudes. PPG students can be open to giving or receiving criticism and suggestions from their fellow students. Generally, students showed positive responses (<90%) toward the learning process; it indicates that the learning process by implementing lesson study is classified in the acceptability category or acceptable to the students.